AL-INTIMĀ' AS-SIMYĀ’IY BAINA JAAKUBSŪN WA AL-BALĀGAH: AL-ITTIJĀH AL-JADĪD FI TAḤLĪL AL-ĀYĀT AL-QUR’ĀNIYYAH - Munjiah, Ma'rifatul; Haque, Arina; Mutholib, Abdul (Annual International Conferences on Language, Literature, and Media, 2022)
Jacobson's semiotics are aligned with rhetoric from the theory of speech, and they are a door through which semiotics enter, as each of them makes the text a communication tool between the two ends of the speaker and the addressee in a specific context with the code to obtain the intended message or meaning. Using them to analyze Quranic verses from two points of view is new because they have the same essential elements. This research is qualitative research by the method of desk study with descriptive analysis that attempts to reveal the code, context, and meanings of the Qur'anic verses from the perspective of Jacobson's semiotics and rhetoric. The analysis is based on the sentence " كُلُوْ " in verse 51 of Surat Al-Muminoon, verse 15 of Surat Al-Mulk, and verse 43 of Surat Al-Mursalat. The result indicates that the code is the same, but the meaning is different; 1) the code "eat" in Surat Al-Mursalat indicates the meaning of honor because the context is in heaven and the addressee is the pious, that is, the permissibility of the pious who enter heaven to eat everything in honor of them from God, 2) and a code " كُلُوْ " in Surat Al-Mulk indicates the meaning of permissibility and what is addressed to people, God has permitted them to seek His sustenance, the Highest, not obligatory because the context is that sustenance on earth is prepared by God not only for people but for all His creatures, people, animals, and others, 3) The code " كُلُوْ " in Surat Al-Muminun indicates On the meaning of obligatory, because the context is the good things and the messengers are addressed, and eating the good things is a duty, that is, the obligation of the messengers to eat the good things or not.